Expediting Disulfiram Assays through a Systematic Analytical Quality by Design Approach - João Basso; Maria Luísa Ramos; Alberto Pais; Rui Vitorino; Ana Fortuna; Carla Vitorino (Chemosensors, 2021)
An Analytical Quality by Design (AQbD) approach is presented, aiming at the development and validation of an HPLC method for the quantification of disulfiram and copper diethyldithiocarbamate in lipid nanoparticles. Following the definition of the analytical target profile (ATP), encompassing the critical analytical attributes (CAA), a two-level risk assessment strategy (Ishikawa diagram—failure mode and effect analysis (FMEA)) was employed to identify the critical method parameters (CMPs) with an extensive impact on method performance. The behavior of the CMPs (flow rate and mobile phase composition) was further characterized by experimental design, resorting to a face-centered central composite design (FcCCD). Statistical modeling, response surface analysis, and Monte Carlo simulations led to the definition of the Method Operable Design Region (MODR), associated with a negligible risk of failing the predefined CAA specifications. The optimal method was validated according to international regulatory recommendations. Apart from guaranteeing linearity, accuracy, precision, specificity, robustness, and stability, these conditions were found to be suitable for analysis using a different HPLC column and equipment. In a nutshell, the development and optimization strategies, under the comprehensive framework of AQbD, provided an effective, simple, rapid, reliable, and flexible method for routine analysis of the compounds in research or industrial environments.